سوشل میڈیاکا مثبت استعمال اورریاستی ذمہ داریاں (سیرت النبی ﷺ کی روشنی میں خصوصی مطالعہ) : Positive Use of Social Media and State Responsibilities Special Study in the Light of Sirat-Un-Nabi (ﷺ) - Dr Majid Nawaz Malik,; Dr Ghulam Hussain Babar, (Al Manhal Research Journal, 2025)
Social media is a platform that combines both good and bad. Its positive use is beneficial, while its negative use is harmful. Thanks to social media, it has become easy to connect with people in any corner of the world. Through social media, various applications, and software, information from around the globe is instantly and easily accessible. A vast treasure of knowledge is now within our reach. Instead of traveling to distant places or searching through countless books, one can now find the desired content in seconds. Qur’anic verses, Hadiths, poetry, religious rulings, dictionaries, and information are available in moments. It is easy to stay informed about national and international affairs, events, and politics. Through platforms like Google Meet, Zoom, and others, people can access online classes, educational videos, and webinars. A large part of society now earns from home through online businesses, marketing, and advertising services. Social media allows people to express opinions on social, political, and various other topics. It is also a means to raise awareness about issues like health, education, human rights, and their solutions. During natural disasters, illnesses, or accidents, social media acts as a rescue platform. It also provides citizens with direct communication access to state institutions. On the other hand, there are several disadvantages as well. Social media is contributing to increasing indecency and misguidance among the younger generation. It spreads fake news and rumors, which creates unrest, anxiety, and fear in society. Youth waste their time on games, posts, videos, and meaningless comments. Through fake accounts, many people are deceived and scammed. Personal information and photos are misused for blackmail and hacking.